2014
DOI: 10.1002/app5.26
|View full text |Cite
|
Sign up to set email alerts
|

The Rentier State at Work: Comparative Experiences of the Resource Curse in East Asia and the Pacific

Abstract: Countries rich in natural resources

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…Recent observers of public spending in Timor-Leste conclude that it 'seems to be enriching elites to a greater degree than before, which is also in line with the expectations of particularist rent distribution associated with clientelist rentier states' (Barma 2014). This may be true, but in respect of the particular case of sub-national spending, this conclusion needs to be nuanced.…”
Section: Central Governmentmentioning
confidence: 84%
“…Recent observers of public spending in Timor-Leste conclude that it 'seems to be enriching elites to a greater degree than before, which is also in line with the expectations of particularist rent distribution associated with clientelist rentier states' (Barma 2014). This may be true, but in respect of the particular case of sub-national spending, this conclusion needs to be nuanced.…”
Section: Central Governmentmentioning
confidence: 84%
“…In the specific and narrow terms of the study reported here, one answer may lie in whether political elites follow through on a few key principles-local consultation, competitive procurement, expenditure transparency, and so onto which they have apparently committed in the PDID Decree. A second, much more speculative response may be found in the wider literature of comparative politics (Slater 2010) and historical institutionalism (Thelen 2004), together with scholarship on the oil curse (for example, Karl 1997;Barma 2014). This might suggest that the flow of oil rents will undermine incentives for elites to coalesce and invest in functional and legitimate public authorities.…”
Section: Resultsmentioning
confidence: 99%
“…3 Ferguson remarks how transnational resource capital tends to 'hop' rather than flow, leaving large gaps between enclave projects and zones passed over(2005: 379). This pattern is, I would argue, characteristic of rentier states such as PNG(Ross 1999;Barma 2014). 4 For further examples, see Handman (2017); Eves (2017); Dalsgaard (2011); Wolffram (2011);Vuvu (2010).…”
mentioning
confidence: 80%
“… Ferguson remarks how transnational resource capital tends to ‘hop’ rather than flow, leaving large gaps between enclave projects and zones passed over (: 379). This pattern is, I would argue, characteristic of rentier states such as PNG (Ross ; Barma ). …”
mentioning
confidence: 84%